Immunization Punctuality in The Achievement of Complete Basic Immunization for Babies Age 12-22 Months in Semarang - Ayun Sriatmi; Wulan Kusumastuti (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2019)
Background : Immunization is an effort that deliberately provides immunity to infants/children to avoid certain diseases. Immunization is important because it affects the growth of infants and children, when administered within the stipulated time period. The facts show that many parents do not immunize on schedule and tend to postpone it. The objectives of the study analyzed the punctuality of complete basic immunization in infants aged 12 to 13 months (“Baduta”) in Semarang.Methods: This research is an observational study with cross sectional design. The population means all Baduta in Semarang, with sample of 689 Baduta from 37 Puskesmas (Society Health Center) taken randomly. Baduta immunization status is obtained from the KIA Book.Results: The results show 98.25% of Baduta have received basic immunization although not all yet complete. Immunization of measles is the most immunization which have not been received yet by Baduta (13.35%),followed by Polio-4 (8.27%) and DPT / HB / HiB-3 (7.4%). Sources of information on immunization are generally obtained from health workers and cadres.Conclusion : Immunization HB-0 is given at the most punctual (96.28%), followed by DPT / HB / HiB-3 (90.13%) and Polio-4 (85.44%), while immunization of measle s has the lowest punctuality (41.04%), followed by BCG immunization (61.5%).